2020
DOI: 10.1038/s41392-020-00280-x
|View full text |Cite
|
Sign up to set email alerts
|

The updated landscape of tumor microenvironment and drug repurposing

Abstract: Accumulating evidence shows that cellular and acellular components in tumor microenvironment (TME) can reprogram tumor initiation, growth, invasion, metastasis, and response to therapies. Cancer research and treatment have switched from a cancer-centric model to a TME-centric one, considering the increasing significance of TME in cancer biology. Nonetheless, the clinical efficacy of therapeutic strategies targeting TME, especially the specific cells or pathways of TME, remains unsatisfactory. Classifying the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
573
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 771 publications
(580 citation statements)
references
References 255 publications
(294 reference statements)
6
573
0
1
Order By: Relevance
“…In solid cancers, the TME can promote immunosuppressive mechanisms, tumor vascularization, growth, and metastasis [26][27][28]. The challenging heterogeneity and dynamic nature of solid tumors, as well as the inherent chemo-resistance present in many tumors, appear to be influenced considerably by the cellular composition of, and interactions within the TME [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In solid cancers, the TME can promote immunosuppressive mechanisms, tumor vascularization, growth, and metastasis [26][27][28]. The challenging heterogeneity and dynamic nature of solid tumors, as well as the inherent chemo-resistance present in many tumors, appear to be influenced considerably by the cellular composition of, and interactions within the TME [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the breadth and the mechanisms of regulatory interactions within the TME is crucial to the development of novel therapeutic options against cancer as well as to a better understanding of the oncogenic process as a whole [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of aspirin use has also been demonstrated in colorectal cancer patients, particularly with PDL1 low tumors [ 176 , 177 ]. However, most of the clinical studies are retrospective, and the therapeutic efficacies of COX inhibitors remain to be determined in clinical settings [ 178 ]. Interestingly, one study reported that treatment with a CDK4/6 inhibitor palbociclib suppressed COX2/PGE2 by the repression of c-JUN expression, resulting in the suppression of cancer metastasis in mouse breast cancer models [ 161 ].…”
Section: Treatments For Cancer Metastasismentioning
confidence: 99%